Ethnic diversity, public goods provision and social cohesion: Lessons from an inconclusive literature - Merlin Schaeffer (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2013)
Over the last two decades there has been a growing debate on the supposedly negative relation between ethnic diversity, public goods production and social cohesion. Despite the amount of evidence, existing in-depth qualitative reviews conclude that the literature is inconclusive. Advancing upon their work, I conduct a quantitative review of over 480 empirical findings from 172 studies. Rather than seeing the huge literature as consisting of an incomparable mass of studies, I argue that the diversity of the literature allows us to analyse the robustness of the general association (does it hold for the comparison of Nepalese villages and European countries alike?) and the conditions under which it is more likely to appear. Accordingly, the review fine-tunes the conclusions we can draw from the existing evidence by noting that the debate has generally produced slightly more confirmatory than confuting evidence. But more importantly, this tendency for validating findings increases considerably under certain conditions: (1) inquiries from regions of the world with rather salient ethnic boundaries, (2) analysis of small-scale neighbourhood contexts and (3) a focus on trust related sentiments or public goods production as outcomes. A rather problematic result of the review is that discipline matters: In comparison to findings published in political science or sociology journals, a considerably larger percentage of findings that are published in economics journals are confirmatory. I conclude by suggesting that interdisciplinary work is necessary and should focus on the conditions under which ethnic diversity is a significant predictor of public goods production and social cohesion.
Keywords: 300; ethnic diversity; social cohesion; social capital; intergroup relations